2007
DOI: 10.1007/s00436-007-0485-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mosquitocidal activity of essential oil and sesquiterpenes from leaves of Chloroxylon swietenia DC.

Abstract: Growing awareness in using ecofriendly and biologically compatible phytoconstituents as natural insecticides and repellents for the safety of life and ecological balance led to conscientious efforts by scientists all over the world to search for alternative sources of plant derivatives for effective use as mosquitocides. Encouraged by this, the essential oil and the sesquiterpenes isolated from the leaves of Chloroxylon swietenia DC. were screened for mosquitocidal activity by fumigant toxicity against three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…In terms of bioactivity, germacrene D has been reported to have insecticidal effects against mosquitoes [34] and to repel aphids [35]. However, it is an attractant to the Tobacco Mudworm Moth, Heliothis virescens [36].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of bioactivity, germacrene D has been reported to have insecticidal effects against mosquitoes [34] and to repel aphids [35]. However, it is an attractant to the Tobacco Mudworm Moth, Heliothis virescens [36].…”
Section: Resultsmentioning
confidence: 99%
“…Mosquitoes also cause allergic responses in humans that include local skin and systemic reactions such as angioedema [3,4]. Culex quinquefasciatus and its complex isomorphic sibling species Anopheles subpictus are major public health problems in India, with around 31 million cases of microfilaraemia, 23 million cases of symptomatic filariasis and about 473 million individuals potentially at risk of infection [4][5][6][7][8][9]. The most medically important species C. quinquefasciatus and A. subpictus breed in water polluted with organic debris, such as rotting vegetation, household refuse and excreta.…”
Section: Introductionmentioning
confidence: 99%
“…The mosquito larvicidal efficacy of Ch. swietenia leaf crude extracts (Jayaraman et al 2015) and leaf essential oil (Ravi kiran et al 2006;Ravi Kiran and Sita Devi 2007;Krishnappa and Elumalai 2012) have shown promising results. However, mosquito larvicidal efficacy of Ch.…”
Section: Introductionmentioning
confidence: 93%